Pengaruh Problem Based Learning Berbantuan E-learning terhadap Kemampuan Berpikir Kritis pada Mata Pelajaran IPA: The Influence of Problem Based Learning Assisted by E-learning on Critical Thinking Skills in Science Subjects - Kurniawati, Inung Diah; Yuda, Yoga Prisma (ITScience (Information Technology and Science), 2024)
The young generation plays a vital role in the government's program towards a golden Indonesia. Therefore, it is necessary to prepare a superior generation to achieve this; improvements are needed in the learning process. Improve the learning process using an appropriate learning model to develop students' critical thinking skills. The learning model chosen in this study is problem-based learning (PBL), assisted by e-learning. Implementing PBL assisted by e-learning in learning is expected to facilitate students in developing critical thinking skills. This study is part of a quasi-experimental study with one group pretest-posttest design. This study was conducted at MTs Ma'arif Ponorogo using a sample of 20 students. The data analysis techniques were the prerequisite test (normality) and the paired t-test difference test. The prerequisite test showed that the data was normally distributed, so further testing was carried out (paired t-test difference test). Based on the results of the data analysis, was the significance value of the related t-test difference test 0.000? 0.05. This result shows a significant difference in the average value of students' critical thinking skills before and after the treatment was given. The students' posttest scores were better than the pretest scores given. This data can be seen from the average pretest score of 52.25 and the average posttest score of 60.00. This shows that PBL effectively develops students' critical thinking skills in collaboration with e-learning users.